Frequency of homologous recombination deficiency in a large community-based cohort of epithelial ovarian cancer cases (597) - Kretzer, Nicole; Musa, Fernanda; Darus, Christopher; Biery, Nancy; Weerasinghe, Roshanthi; Li, Hsin- Fang; Vita, Ann; Pindikuri, Shwetha; Parrish, Amy; Drescher, Charles (Gynecologic oncology, 2022)
Objectives: Homologous recombination deficiency (HRD) is a useful predictor of treatment response in patients with epithelial ovarian cancer (EOC). Reported data on the frequency of HRD in EOC is largely based on analysis of patients treated at academic medical centers or who participated in clinical trials. We sought to characterize the frequency of HRD based on mutations in homologous recombination repair (HRR) genes, genomic instability (GI), and loss of heterozygosity (LOH) scores in a large community-based cohort of EOC patients who received genomic testing in the context of routine clinical care. Methods: Information including patient demographic, tumor stage and histology data, and results from ovarian cancer tumor tissue sequencing tests was obtained from the diverse dataset within the Providence St. Joseph Health (PSJH) Electronic Medical Record (EMR) and the system-wide cancer registry data. Patients with an EOC diagnosis (ICD C56.x) between January 2015 and January 2020 were included. Structured genomic data was sourced from laboratory information systems and manual abstraction of molecular sequencing reports. Alterations in the following HRR genes were analyzed, along with LOH and GI scores: ATM, BARD1 BRCA1 BRCA2, BRIP’, CDK’2, CHEK’, CHEK2, FANCL, PALB2, PPP2R2A, RAD“’B, RAD“’C, RAD“’D, RAD“4L. Results: Within this EOC cohort of 3007 patients, 510 (17%) had tumor tissue sequencing (TTS) ordered in the context of clinical care. TTS increased over time (p<0.0001) and was more frequent in patients with advanced-stage disease (33/392 vs 149/659 for Stage I-II vs Stage III-IV, X2=34.6, p < 0.00001) or who had a tissue biopsy at a PSJH facility (214/1,151 vs 139/998 for biopsy vs no biopsy, X2=8.5, p=0.004). Eight patients (1.5%) had an insufficient tissue sample despite multiple attempts. Pathogenic mutations in HRR genes were identified in 97 (19%) patients, including BRCA’ (n=54), BRCA 2 (n=25), ATM (n=9), CHEK2 (n=6), PALB2 (n=2) and BRIP1 (n=1). LOH and GI scores reflective of HRD were noted in 34/115 (30%) and 9/40 (23%) of patients tested, respectively. HRR gene mutations and/or GI/LOH were identified in tumors of all stages. Treatment data were available for a subset of patients. Patients with mutations or GI/LOH were far more likely to receive PARPi maintenance therapy than patients without these findings (Table 1). Conclusions: In this large, community-based cohort of EOC cases, commercial TTS identified evidence of HRD in 151 of 510 (27%) patients tested. Molecular alterations were identified in tumors of all stages, suggesting that broad-based TTS may be of value. A large fraction of patients with HRD may not be receiving indicated PARPi therapy.